Guest Editorial Special Issue on Continual Unsupervised Sensorimotor Learning - Navarro-Guerrero, Nicolas; Nguyen, Sao Mai; Oztop, Erhan; Zhong, Junpei (IEEE transactions on cognitive and developmental systems, 2021)
The pursuit of higher levels of autonomy and versatility in robotics is arguably led by two main factors. First, as we push robots out of the labs and production lines, it becomes increasingly challenging to design for all possible scenarios that a particular robot might encounter. Second, the cost of designing, manufacturing, and maintaining such systems becomes prohibitive.